Disaster Preparedness and Mitigation in Indonesia: A Narrative Review - Dumilah Ayuningtyas; Sri Windiarti; M Sapoan Hadi; Ulya Uti Fasrini; Sandra Barinda (Tehran University of Medical Sciences, 2021)
Background: The tectonic activities at the meeting points of three large plates make Indonesia a high-risk disaster-prone area. Nevertheless, disaster risk reduction efforts in various regions of Indonesia are still lacking, in terms of both knowledge and the ability to analyze disaster risks. This study examines the implementation of disaster preparedness and mitigation in Indonesia. Methods: The method used in this study was narrative review. The authors collected the articles through searching for 3 data sources from 2016-2019 using Google Scholar, iSeek, and Microsoft Academic. Content analysis of all information to obtain the thematic phenomena of this study completed the methodological approach. Results: After applying the exclusion criteria and removing duplicates, six studies remained that focused on disaster mitigation in remote areas of Indonesia. Implementation of regulation and policy framework in disaster management is not yet optimal. Disaster preparedness and mitigation is characterized by the low utilization of technology and information related to the disaster, and various obstacles in the process of evacuation and transportation. Promoting local wisdom and enhancing it through integrating science can increase disaster resilience. Conclusion: The existence of a disaster-resilient village is very influential in community preparedness in dealing with disasters and other emergencies. This study provides some recommendations for disaster risk reduction: a) strengthening policies related to evacuation procedures in the health sector by local government, b) integrating transportation modes in remote areas, c) enhancing all parties with education and training, d) establishing community-based information systems; and e) strengthening the disaster resilience of villages.